2017
DOI: 10.1093/hmg/ddx144
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory chain enzyme deficiency induces mitochondrial location of actin-binding gelsolin to modulate the oligomerization of VDAC complexes and cell survival

Abstract: Despite considerable knowledge on the genetic basis of mitochondrial disorders, their pathophysiological consequences remain poorly understood. We previously used two-dimensional difference gel electrophoresis analyses to define a protein profile characteristic for respiratory chain complex III-deficiency that included a significant overexpression of cytosolic gelsolin (GSN), a cytoskeletal protein that regulates the severing and capping of the actin filaments. Biochemical and immunofluorescence assays confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…Only one contradiction was found: the GSN gene was found to be down-regulated in our study, yet up-regulated in one in vivo study [17]. GSN encodes Gelsolin, which regulates actin assembly and has also been associated with inhibiting apoptosis [41]. The reason for this discrepancy is unknown; it could be because our experiment characterized gene expression at 18 h p.i., whereas the in vivo study was conducted at 3 and 4 days p.i.…”
Section: Discussionmentioning
confidence: 56%
“…Only one contradiction was found: the GSN gene was found to be down-regulated in our study, yet up-regulated in one in vivo study [17]. GSN encodes Gelsolin, which regulates actin assembly and has also been associated with inhibiting apoptosis [41]. The reason for this discrepancy is unknown; it could be because our experiment characterized gene expression at 18 h p.i., whereas the in vivo study was conducted at 3 and 4 days p.i.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies in mitochondrial complex III (CIII)-deficient cell lines revealed a specific upregulation of cytosolic GSN and its localization to the mitochondrial outer membrane (mGSN), where it interacts with VDAC1 to promote protective antiapoptotic responses [ 12 , 40 ]. To discriminate whether this phenomenon is specific to CIII deficiency, rather than occurring as a general response to OXPHOS enzyme defects, we analyzed control and mutant cybrids with different types of OXPHOS deficiency ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To exclude that these effects were specific to cybrid cell lines, we tested pGSN levels in the secretomes from primary cultured fibroblasts from patients harboring pathogenic mutations in the complex III assembly factor BCS1L ( Figure 3 A), which previously showed a marked respiratory chain dysfunction [ 12 ] together with an upregulated expression and mitochondrial location of GSN ( Table 3 ) [ 40 ]. SDS-PAGE gels were stained with Coomassie blue and densitometric measurements per lane were used as loading controls for the normalization of subsequent pGSN immunoreactive signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one contradiction was found: the GSN gene was found to be down-regulated in our study, yet up-regulated in one in vivo study (17). GSN encodes Gelsolin, which regulates actin assembly and has also been associated with inhibiting apoptosis (40). The reason for this discrepancy is unknown; it could be because our experiment characterised gene expression at 18 hours post-infection, whereas the in vivo study was conducted at 3 and 4 days post infection.…”
Section: Discussionmentioning
confidence: 99%